2009
DOI: 10.1167/9.6.17
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral optical errors and their change with accommodation differ between emmetropic and myopic eyes

Abstract: The progression of myopia is thought to be controlled by the retinal image quality, but its triggering factors are not yet well known. The differences between the peripheral optics in emmetropic and myopic eyes might explain why some eyes become myopic. The present study further investigates peripheral optical quality and how it is affected by accommodation. The refraction and aberrations of the right eyes of five emmetropes and five myopes were measured using a laboratory Hartmann-Shack wave front sensor, spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
83
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 46 publications
15
83
1
3
Order By: Relevance
“…First, defocus showed large differences between individuals in how it varied with the off-axis angle over the temporal and nasal halves, as earlier noted by Gustafsson and co-workers and Ferree and colleagues [5,26]. Secondly, the higher-order aberrations tended to be larger in the nasal visual field, which can also be seen for astigmatism in Figure 3 and in the figures of references [2,3,21,23].…”
Section: Emsupporting
confidence: 62%
See 1 more Smart Citation
“…First, defocus showed large differences between individuals in how it varied with the off-axis angle over the temporal and nasal halves, as earlier noted by Gustafsson and co-workers and Ferree and colleagues [5,26]. Secondly, the higher-order aberrations tended to be larger in the nasal visual field, which can also be seen for astigmatism in Figure 3 and in the figures of references [2,3,21,23].…”
Section: Emsupporting
confidence: 62%
“…These were one laboratory Hartmann-Shack sensor in Murcia, Spain, which has been previously used for peripheral measurements [21,22], and one commercial Hartmann-Shack (COAS-HD-VR) sensor in Kalmar, Sweden, which has been shown to provide repeatable measurements of peripheral aberrations [23]. In total, there were 22 subjects.…”
Section: Methodsmentioning
confidence: 99%
“…According to Shen and colleagues soft contact lenses do not have a consistent effect on peripheral relative blur 30 whilst others showed that axial correction increases the precision of offaxis refractive error measurements. 31 However, soft contact lens have an effect on relative peripheral refraction (field curvature) that we discuss below. Thus, during measurements participants with myopia were compensated with a spherical contact lens (Focus Dailies®, Ciba Vision Corporation) to correct on-axis refractive error, the power of the lens was the spherical equivalent.…”
Section: Methodsmentioning
confidence: 99%
“…The progression of myopia is thought to be controlled by the retinal image quality, but its triggering factors have not been yet well known (Lundstrom, Mira-Agudelo, & Artal, 2009). In a large number of studies, children with myopic parents are more likely to have myopia than those without myopic parents (Guggenheim, Kirov, & Hodson, 2000;Mutti et al, 2002;Mutti & Zadnik, 1995;Saw, Nieto, et al, 2001; M. M. Wu & Edwards, 1999;Young, 2009).…”
Section: Risk Factors Related To the Refractive Errormentioning
confidence: 99%